2020
DOI: 10.1093/deafed/enaa012
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Personal Resiliency in Deaf and Hard-of-Hearing Adolescents

Abstract: Hearing loss is a risk factor for a child’s appropriate psychosocial development but is not a risk factor for the development of resiliency. Thus, the aim of this research was to determine the level of resiliency, as well as its relation to internal and external factors, in deaf and hard-of-hearing (DHH) adolescents. The sample included 55 DHH students, 12–14 years of age. Resiliency Scales for Children & Adolescents was used in this research. The obtained results showed that DHH students perceived their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…In other words, the deaf children of deaf parents may enjoy more robust academic involvement of fathers (Musyoka, 2015) as compared to the deaf children of hearing parents. Ricci and Hodapp (2003) in their study failed to indicate the contribution of the type and/or severity of a disability on the interaction between fathers and their deaf children; while other studies have indicated a correlation between the type and/or severity of a disability and the concentration of fathers' commitment to the overall development and wellbeing of their deaf children (Konstantareas & Homatidis, 1992;Radovanović et al, 2020). Radovanović et al (2020) argued that the development of social competencies and academic resilience among deaf children is influenced by the interaction of external and internal variables.…”
Section: Literature Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…In other words, the deaf children of deaf parents may enjoy more robust academic involvement of fathers (Musyoka, 2015) as compared to the deaf children of hearing parents. Ricci and Hodapp (2003) in their study failed to indicate the contribution of the type and/or severity of a disability on the interaction between fathers and their deaf children; while other studies have indicated a correlation between the type and/or severity of a disability and the concentration of fathers' commitment to the overall development and wellbeing of their deaf children (Konstantareas & Homatidis, 1992;Radovanović et al, 2020). Radovanović et al (2020) argued that the development of social competencies and academic resilience among deaf children is influenced by the interaction of external and internal variables.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Ricci and Hodapp (2003) in their study failed to indicate the contribution of the type and/or severity of a disability on the interaction between fathers and their deaf children; while other studies have indicated a correlation between the type and/or severity of a disability and the concentration of fathers' commitment to the overall development and wellbeing of their deaf children (Konstantareas & Homatidis, 1992;Radovanović et al, 2020). Radovanović et al (2020) argued that the development of social competencies and academic resilience among deaf children is influenced by the interaction of external and internal variables. Among the external variables are culture, educational programmes, availability of instructional resources, and robust interpersonal relationships between the children and the adults (Radovanović et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…Resilience is a positive adaptation that is capable of restoring ones' mental health by keeping a balance of physical and psychological functioning despite adversities, level of risk, threats or hardship (Wald et al, 2006). In recent times, the concept of 'resilience' is gathering momentum, especially in the wake of COVID-19, and the concept has been examined in different dimensions (Radovanović et al, 2020).…”
Section: Literature Review Deaf Learners and Academic Resiliencementioning
confidence: 99%